1992
DOI: 10.1161/01.hyp.19.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium salts on pressor reactivity in salt-sensitive men.

Abstract: Blood pressure in patients with essential hypertension is raised by sodium chloride but not by nonchloride sodium salts. Although a high sodium chloride diet is known to augment the pressor response to norepinephrine and angiotensin II, the effect of nonchloride sodium salts on pressor responsiveness has not been studied so far. To examine whether sodium chloride and nonchloride sodium salts evoke different pressor responses to these agonists, we performed graded norepinephrine and angiotensin II infusions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Our data show that the magnitude of the AngI and AngII responses was larger during liberal sodium intake as an independent variable in the multiple regression analysis. This is in accord with similar findings in normal subjects, and has been attributed to up-regulation of the sensitivity of AngII receptors during high sodium intake [25,26,27]. On multivariate analysis we found that sodium intake also modified the effect of ACE genotype on AngI response, independent from AngII response.…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that the magnitude of the AngI and AngII responses was larger during liberal sodium intake as an independent variable in the multiple regression analysis. This is in accord with similar findings in normal subjects, and has been attributed to up-regulation of the sensitivity of AngII receptors during high sodium intake [25,26,27]. On multivariate analysis we found that sodium intake also modified the effect of ACE genotype on AngI response, independent from AngII response.…”
Section: Discussionsupporting
confidence: 91%
“…However, we also showed that during low‐salt diet the SS‐Index is positively associated with cardiac output and arterial compliance and negatively associated with SVR and characteristic impedance, suggesting a residual positive salt balance in SS subjects during salt depletion and giving support to Guyton's physiology. We may also hypothesize a role played by altered modulations of the renin–angiotensin–aldosterone system or of the sympathetic nervous system, reported to occur in hypertensive SS individuals 3, 27. However, studies in normotensive humans revealed that an increased dietary salt intake (5–7 days of high‐salt regimen) induces a profound reduction in vascular nitric oxide bioavailability, which limits endothelium‐dependent vasodilation 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the simultaneous absorption of halogen ions like Cl-or I-with Na+ has been shown to potentiate hypertension (20). For the prevention and medical treatment of hypertension, it has been generally accepted that limiting the dietary salt intake in daily life is important (25). On the other hand, a relationship between hypertension and vitamin C has been recently discovered.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that the difference in the sensitivity to salt is caused by multiple genetic patterns (24). It has been studied whether or not Na+ or Cl-ions are mainly responsible for high blood pressure (25). There have been two different discussions regarding the effects of salt and vitamin C on the increment or sup pression of high blood pressure.…”
mentioning
confidence: 99%